Old age risks, consumption, and insurance - Richard W. Blundell; Margherita Borella; Jeanne Commault; Mariacristina De Nardi (Institute for Fiscal Studies (IFS), 2023)
In the U.S, after age 65, households face income and health risks and a large fraction of these risks are transitory. While consumption significantly responds to transitory income shocks, out-of-pocket medical expenses do not. In contrast, both consumption and out-of-pocket medical expenses respond to transitory health shocks. Thus, most U.S. elderly keep their out-of-pocket medical expenses close to a satiation point that varies with health. Consumption responds to health shocks mostly because adverse health shocks reduce the marginal utility of consumption. The effect of health on marginal utility changes the optimal transfers due to health shocks.
Keywords: 330